Archaeology and buddhism in South Asia - Ray, Himanshu Prabha (London : Routledge, Taylor & Francis Group, 2018)
This book traces the archaeological trajectory of the expansion of Buddhism and its regional variations in South Asia. Focusing on the multi-religious context of the subcontinent in the first millennium BCE, the volume breaks from conventional studies that pose Buddhism as a counter to the Vedic tradition to understanding the religion more integrally in terms of dhamma (teachings of the Buddha), dana (practice of cultivating generosity) and the engagement with the written word. The work underlines that relic and image worship were important features in the spread of Buddhism in the region and were instrumental in bringing the monastics and the laity together. Further, the author examines the significance of the histories of monastic complexes (viharas, stupas, caityas) as also religious travel and pilgrimage that provided connections across the subcontinent and the seas. An interdisciplinary study, this book will be of great interest to students and scholars in South Asian studies, religion, especially Buddhist studies, history and archaeology.
Includes bibliographical references and index.
Keywords: Buddhism -- South Asia. -- Buddhist antiquities -- South Asia. -- Excavations (Archaeology) -- South Asia. -- South Asia -- Buddhism -- Buddhist antiquities -- a